Nasal carriage rate and multiple antimicrobial resistance indices of Staphylococcus aureus among healthcare students at the Ahmadu Bello University, Nigeria - Sumayya Abdullahi; Idris N. Abdullahi; Hafeez A. Adekola; Nicholas Baamlong; Amos Dangana; Yahaya Usman; Abdurrahman E. Ahmad; Sumaiya Salisu; Mukhtar M. Abdulaziz (African Journal of Laboratory Medicine, 2025)
Background: Healthcare students could harbour multidrug-resistant (MDR) and methicillin-resistant Staphylococcus aureus (MRSA). There is a need to understand the extent and factors associated with nasal carriage of these strains.